If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5-4-3x=-36
We move all terms to the left:
5-4-3x-(-36)=0
We add all the numbers together, and all the variables
-3x+37=0
We move all terms containing x to the left, all other terms to the right
-3x=-37
x=-37/-3
x=12+1/3
| p/2=1.54 | | 3x+(x-14)=33 | | 8u=456 | | 8u=455 | | n+(n+1)+(n+2)+(n+3)+55=3(n+4) | | c/27=7 | | -5y(y-5)=-3y+45 | | 8-2(12+12)=5-2x-13 | | 5-4|-3x|=-36 | | r-5=43 | | -4b=-8-6b^2+4b | | c+25=671 | | 4+9.75x=0.25x+ | | 5+5(n-1)=19 | | -(x+3)+4x=6 | | n+(n+1)+(n+2)+(n+3)+(n+4)=55 | | 10+7.5n=8+7.9n | | 128=k-39 | | h+94=891 | | (2x+7)=65 | | v+9-48=1 | | h+94=894 | | –17+15z=13z+19 | | 2n+8=60 | | 459=27g | | n+(n+1)+(2(n+2)+2(n+3)+55)=3(n+4) | | 634=p+551 | | H=210+33x | | 162+24.50x=4.25 | | -x2+2x=3 | | 4c+2c=4 | | 70x-60=-20x-42 |